Cleaning School Buildings and Introducing Waste Management to Improve the Quality of Settlements - Lintang Satiti Mahabella; Amalia Nur Adibah; Yunan Rusdianto; Azhar Adi Darmawan (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Kalisongo Village is located in Malang Regency with a topography consisting of 60% undulating plains and 40% hilly undulating plains, with increasingly steep slopes to the west. The main focus of this community service activity is to improve the quality of settlements by enhancing waste management systems by providing trash bins and cleaning school facilities to support the comfort of kindergarten students. In Kalisongo Village, the condition of the Dharma Wanita Persatuan 1 Kalisongo kindergarten school building is quite concerning due to its location in an alley and the impact of the pandemic on the quality of school facilities. The residential area in Kalisongo Village already has a waste transportation system to the Supit Urang landfill, with waste being collected by designated personnel from each household. Residents place their waste in front of their houses without trash bins, often leading to scattered waste, affecting the cleanliness and aesthetics of the environment. This community service was carried out using the Participatory Action Research (PAR) method, involving activities to improve and enhance learning facilities for kindergarten students and increase awareness of household waste management through socialization and the placement of trash bins in each household. This aimed to boost residents' enthusiasm for managing waste and maintaining a clean environment. The activity was conducted from September to December 2022 and successfully improved the cleanliness and comfort for Dharma Wanita Persatuan 1 Kalisongo kindergarten students and the residents of Kalisongo Village. This is evidenced by the enthusiasm of the 38 kindergarten students welcoming a cleaner school building and the active participation of residents in waste management introduction and the distribution of 30 trash bins to village residents.